Design of Elementary Social Sciences Learning Techniques and Tactics - Syafruddin, Syafruddin; Deswita, Ririn; Amelya, Amelya; sastri Ananta, Ayu; Tinatun, Tinatun (JUPE : Jurnal Pendidikan Mandala, 2024)
This research aims to develop and evaluate the effectiveness of technical and tactical designs in learning Social Sciences (IPS) at the elementary school (SD) level. The approach used in this research is a qualitative method with data collection techniques through observation, interviews and documentation studies. The research results show that learning designs that involve visualization techniques, problem solving, and active student involvement can improve students' conceptual understanding and social skills. Learning techniques such as the use of mind maps, role playing, and case studies have proven effective in facilitating in-depth understanding of social studies material. The learning tactics implemented include setting up a conducive learning environment, integration of information technology, and a project-based learning approach that emphasizes student cooperation, critical thinking, and creativity. The evaluation results show a significant increase in student motivation for learning achievement. This study provides new insights into social studies learning practices in elementary schools and suggests several recommendations for developing curriculum and teaching practices in the future.